Competing magnetic states and M–H loop splitting in core–shell NiO nanoparticles. (20th August 2022) - Abbas, Hur; Nadeem, K; Hester, J; Pervez, M F; Yick, S; Kostylev, M; Letofsky-Papst, Ilse; Ali, B; Ulrich, C; Krenn, H
Abstract: Magnetic relaxation in a nanoparticles system depends on the intra-particle interactions, reversal mechanism, the anisotropy field, easy axis distribution, particle volume, lattice defects, surface defects, materials composite, etc. Here we report the competing magnetic states between superparamagnetic blocking and Néel transition states in 14 nm core–shell NiO nanoparticles. A crossover temperature of 50 K was observed for both these states from the zero field cooled/field cooled magnetization curves taken at different fields. At crossover temperature, an interesting M – H loop splitting is observed which is attributed to the slow spin relaxation. This anomalous M – H loop splitting behaviour was found to be particle size dependent and suppressed for diameters above and below 14 nm which indicates a critical size for these competing magnetic states. Additional neutron diffraction experiments confirmed this observation. This experimental study provides a new insight for the understanding of intra-particle interactions in fine antiferromagnetic nanoparticles and obtained results are an important step towards deeper understanding of the competing/non-competing modes between superparamagnetic blocked and Néel transition states.